2016
DOI: 10.1186/s12864-016-2778-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple adaptive routes of Salmonella enterica Typhimurium to biocide and antibiotic exposure

Abstract: BackgroundBiocides and antibiotics are used to eradicate or prevent the growth of microbial species on surfaces (occasionally on catheters), or infected sites, either in combination or sequentially, raising concerns about the development of co-resistance to both antimicrobial types. The effect of such compounds on Salmonella enterica, a major food-borne and zoonotic pathogen, has been analysed in different studies, but only few works evaluated its biological cost, and the overall effects at the genomic and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Co-selection is achieved in two ways: (1) co-resistance, whereby selection for one gene fosters the maintenance of another resistance gene, one that does not necessarily offer a selective advantage to the chemical in question (Johnson et al, 2016); and (2) cross-resistance, whereby one resistance gene can offer protection from multiple toxic chemicals (Curiao et al, 2016). Co-resistance is analogous to bringing a toolbox to a worksite; one might only need one or two tools from the toolbox at any one time, but there are many tools ‘fortuitously’ available for use should the need arise.…”
Section: Fundamental Questions Of Amr In the Environment: What Are Thmentioning
confidence: 99%
“…Co-selection is achieved in two ways: (1) co-resistance, whereby selection for one gene fosters the maintenance of another resistance gene, one that does not necessarily offer a selective advantage to the chemical in question (Johnson et al, 2016); and (2) cross-resistance, whereby one resistance gene can offer protection from multiple toxic chemicals (Curiao et al, 2016). Co-resistance is analogous to bringing a toolbox to a worksite; one might only need one or two tools from the toolbox at any one time, but there are many tools ‘fortuitously’ available for use should the need arise.…”
Section: Fundamental Questions Of Amr In the Environment: What Are Thmentioning
confidence: 99%
“…For instance, STTR5 is located between two domains of YohM, a protein involved in nickel and cobalt resistance (Rodrigue et al, 2005). STTR3 is located between a signal peptide and a polypeptide chain in BigA, a surface-exposed virulence protein (Curiao et al, 2016). The extreme length in STTR5 or STTR3 may affect the stability of YohM and weaken the resistance to nickel and cobalt or reduce the virulence of BigA by interfering with the signal peptide and/or affecting the protein secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of wastewater and processes applied in WWTP may select for resistant bacteria and enhance their growth compared to non-resistant strains [10,[12][13][14][15]. We measured viable cell count of the strains before and after induction.…”
Section: Antibiotic Resistance Induction In Wwtpmentioning
confidence: 99%
“…These characteristics of wastewater and processes applied in WWTP are suspected to help enhance the generation and replication of ARB. In vitro studies showed that detergent, antibiotics, chlorine and biocides may induce antibiotic resistance in bacteria and select for resistant strains [10,[12][13][14][15]. However, whether, how and which processes in WWTP may induce resistance need further investigation.…”
Section: Introductionmentioning
confidence: 99%